PROBING THE POTENTIAL FOR FUNCTIONAL RECOVERY IN PATIENTS WITH NEUROMYELITIS OPTICA USING VISUOMOTOR PRACTICE. Issue 11 (9th October 2013) - John, Bethan E; Luppe, Sebastian; Khirwadkar, Hannah; Smalley, Michelle; Hourihan, Margaret; Robertson, Neil; Tomassini, Valentina
Abstract : Objective: Neuromyelitis optica (NMO) is characterised by episodes of optic neuritis and transverse myelitis. Despite therapeutic advances, treatments aimed at reducing disease activity have little impact on disabilities and much of the patients' management is focused on optimizing function. Functional recovery is supported by adaptive brain functional reorganization ("plasticity") that also occurs with the acquisition of new skills. Here, we use practice of new visuomotor skills to probe the potential for functional recovery in NMO. Since NMO damage typically affects the spinal cord and optic nerve, which are functional "bottlenecks", we hypothesise that the ability to improve performance through practice, reflecting plasticity underlying recovery, is impaired in these patients. Methods: Visual (LogMAR), motor (grip strength, 9–Hole Peg test, 25–Feet Timed Walk) and cognitive functions, including speed of processing (Digit Symbol–Coding), executive functions (Oral Trails) and sustained attention (PASAT), were tested in 17 NMO patients and 21 age–and sex–matched healthy volunteers, prior to practicing a right–handed visuomotor tracking task. Participants tracked on a computer screen the movement of a computer–controlled bar oscillating in either a repetitive (Sequence) or random (Random) fashion. Visuomotor improvements were quantified as the reduction in mean tracking error with practice. Brain and spinal cord lesions were identified on the available clinical magnetic resonance imaging (MRI) scans. Results: Out of 17 NMO patients (mean±SD disease duration 6.9±5.7 years; mean±SD number of relapses 3.9±2.5 years; median EDSS, 4.0, range 1.5–7.0; mean±SD time since last relapse 2.9±4.3 years), 12 had a history of both transverse myelitis and optic neuritis, and 5 of acute transverse myelitis only. Patients significantly differed from controls in visual and cognitive functions, as well as in right–handed strength and dexterity, and walking time. Out of 71% of patients for whom brain MRI was available, 83% had visible brain damage, particularly in the frontal and parietal lobes. Spinal cord MRI was available in 76% of patients, 85% of whom had visible cord lesions. There was no significant difference in initial visuomotor performance and improvements with practice between patients and controls. The level of visuomotor performance improvements did not correlate with behavioral measures or clinical disability in patients. In controls, poorer initial performance correlated with faster improvements in Sequence and in Random. This relationship was present in Random, but not in Sequence for patients. In patients, greater motor improvements in Sequence correlated with higher PASAT scores. Conclusion: Refuting our initial hypothesis, we found that visuomotor improvements in patients were comparable to those of healthy volunteers, suggesting that plasticity is preserved in NMO. Damage to functional "bottlenecks" did not appear to be a factor in preventing visuomotor improvement with practice, suggesting that the limits of adaptive plasticity in NMO may result from a complex interaction between distribution, location and type of damage. The effect of cognitive dysfunction on the ability to improve performance in the more cognitively demanding task condition emphasises the importance of tailoring recovery–oriented interventions in NMO to the patients' cognitive abilities.